Combination Therapy of Half-Dose Resmetirom and Metformin Attenuates Metabolic Dysfunction-Associated Steatohepatitis Through Improving Cholesterol Metabolism and Inflammation - Wenxiu Liu; Fan Yao; Jinghan Wang; Nan Shao; Xinxin Cao; Zhengqi Dong; Bin Zhang; Xiaobo Sun (Biomedicines)
Background/Objectives: Metabolic dysfunction-associated steatohepatitis (MASH) has become the leading cause of hepatocellular carcinoma and liver disorders globally. Nevertheless, only one expensive drug, resmetirom (Res), has been approved by the FDA for MASH treatment to date. However, its high price has imposed a heavy financial burden on patients. Methods: In this study, half-dose Res and low-dose metformin (Met) (referred to as RM) were administered in combination to treat MASH models in vitro and in vivo. We utilized transcriptome and lipidomics sequencing to assess the efficacy of RM in improving MASH. Our goal was to systemically compare the therapeutic effects of RM, Met, and Res on MASH and elucidate the underlying mechanisms. Results: Our results demonstrated that RM was comparable to Res and superior to Met in reducing lipid production in vitro, attenuating lipid accumulation, inhibiting inflammation, and improving fibrosis in vivo. Transcriptome and lipidome analyses further revealed that RM regulated the expression of genes and lipids in a manner similar to Res, particularly in pathways related to cholesterol metabolism and inflammation. Further validation showed that RM facilitated cholesterol transformation by robustly promoting the expression of CYP7A1, thereby mitigating MASH. Conclusions: Collectively, our findings highlight that a combination of half-dose Res and Met is equivalent to Res alone in terms of MASH treatment efficacy. This study provides a novel therapeutic strategy that is not only effective for MASH treatment but also reduces the economic burden on patients.